Government Buildings, Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
Exterior view of the government building, the Red House in Port of Spain, Trinidad. A man is seen standing at left foreground of the building.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historic buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Red House, The